a stone is thrown the air from the ground so as to just clear top of two wall of heights 'a' and 'b' at distances 'b' and 'a' respectively from the point of projection. then what is the tan of angle of projection?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let the times the stone, with a projected velocity v at an angle θ with the horizontal, clears the tops of the first and second walls be t 1 and t 2 respectively. Therefore, t 1 = u cos θ b , t 2 = u cos θ a and a = u sin θ t 1 − 2 1 g t 1 2 , b = u sin θ t 2 − 2 1 g t 2 2 Therefore, a = u sin θ u cos θ b − 2 1 g ( u cos θ b ) 2 a = b tan θ − 2 u 2 g b 2 sec 2 θ ÷ b 2 throughout: b 2 a = b tan θ − 2 u 2 g sec 2 θ Similarly, for the equation for b , we have: a 2 b = a tan θ − 2 u 2 g sec 2 θ Subtracting the above two equations: b 2 a − a 2 b = ( b 1 − a 1 ) tan θ a 2 b 2 a 3 − b 3 = a b a − b tan θ tan θ = a b a 2 + a b + b 2 = 1 + b a + a b
Let the projectile travel a distance of 'b' when it's is at a height of 'a'. Let the initial velocity of projection be 'u' at an angle of 'x'. In X-axis b=ucos (x) t where 't' is the time the projectile takes to cover 'b'. therefore t=b/(ucos(x)) and In Y-axis a=usin(x) t-(g/2) (t^2)) putting the value of t in this equation, we obtain a=btan(x)-5 (b^2)/((ucos(x)^2))---------------------------(eqn-1)
Let the projectile travel a distance of 'a' when it's is at a height of 'b'. Let the initial velocity of projection be 'u' at an angle of 'x'. In X-axis a=ucos (x) t1 where 't1' is the time the projectile takes to cover 'b'. therefore t1=a/(ucos(x)) and In Y-axis b=usin(x) t-(g/2) (t1^2)) putting the value of t1 in this equation, we obtain b=atan(x)-5 (a^2)/((ucos(x)^2))------------------------------(eqn-2)
equate both the equations with the help of ((u*cos(x))^2) to obtain the answer.
Problem Loading...
Note Loading...
Set Loading...
Equation of trajectory of the particle, y = x tan θ ( 1 − R x ) .
a = b tan θ ( 1 − R b ) . . . . . . . . . . . . . (1).
b = a tan θ ( 1 − R a ) . . . . . . . . . . . . . . . .(2).
Hence, b 2 a 2 = R − a R − b .
R = a 2 − b 2 a 3 − b 3 .
By substituting the value of R in any of the above equations, we will get the value of tan θ = b a + a b + 1 .